2016
DOI: 10.1038/srep38914
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a LOS and a capsular polysaccharide in Capnocytophaga canimorsus

Abstract: Capnocytophaga canimorsus is a dog’s and cat’s oral commensal which can cause fatal human infections upon bites or scratches. Infections mainly start with flu-like symptoms but can rapidly evolve in fatal septicaemia with a mortality as high as 40%. Here we present the discovery of a polysaccharide capsule (CPS) at the surface of C. canimorsus 5 (Cc5), a strain isolated from a fulminant septicaemia. We provide genetic and chemical data showing that this capsule is related to the lipooligosaccharide (LOS) and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(38 citation statements)
references
References 81 publications
(120 reference statements)
2
35
0
1
Order By: Relevance
“…Tenacibaculum species on the other hand are commonly associated with marine organisms such as sponges and macroalgae (Suzuki et al, 2001), with T. maritimum recognized as an important pathogen on marine fish (Pérez-Pascual et al, 2017). Among the three non-marine groups, the group IIa is composed exclusively of the genus Capnocytophaga, which is an oral commensal lineage in animals but that can cause fatal infections in humans (Manfredi et al, 2011;Renzi et al, 2016). The non-marine group III is comprised of the genera Flavobacterium and Myroides.…”
Section: Resultsmentioning
confidence: 99%
“…Tenacibaculum species on the other hand are commonly associated with marine organisms such as sponges and macroalgae (Suzuki et al, 2001), with T. maritimum recognized as an important pathogen on marine fish (Pérez-Pascual et al, 2017). Among the three non-marine groups, the group IIa is composed exclusively of the genus Capnocytophaga, which is an oral commensal lineage in animals but that can cause fatal infections in humans (Manfredi et al, 2011;Renzi et al, 2016). The non-marine group III is comprised of the genera Flavobacterium and Myroides.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, C. canimorsus mostly frequently causes systemic infections in humans, the mortality rate of such sepsis being 26% . C. canimorsus can reportedly escape from the bactericidal activity of the innate immune system and is able to deglycosylate human IgM . C. cynodegmi and C. stomatis are occasionally associated with wound infections .…”
mentioning
confidence: 99%
“…In our previous work, we showed that C. canimorsus is endowed with capsular polysaccharides and that the majority of human-isolated strains exhibit capsule type A, B, or C, suggesting that these three capsular serovars are more virulent to humans 13 , 14 . In this study, we confirmed the prevalence of C. canimorsus capsular serovars A, B, and C in a larger collection of human-isolated strains.…”
Section: Discussionmentioning
confidence: 95%
“…The commonality of some capsular serovars in these three species might result from genetic transfers of the capsular genes. This hypothesis is supported by the genetic organization of the C. canimorsus capsular genes, which are organized in loci including genes coding for transposases 13 . Whether Capnocytophaga species exchange their capsular genes is an open question that requires further investigation.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation